Analysis of Madrasah Ibtidaiyah Prospective Teachers’ Ability to Identify Scientific Arguments in Research Articles - Suprapti; Anggrella, Dita Purwinda; Sudrajat, Ahmad Kamal (Jurnal Pendidikan Islam, 2023)
Purpose – This study aims to investigate students' proficiency in analyzing scientific arguments within research papers, a critical skill for successfully composing a thesis project. Despite its importance, many students struggle to interpret scientific literature effectively as a reference source in their research. Therefore, this research evaluates students' abilities to identify various elements of scientific arguments in academic works. Design/methods/approach – Adopting a quantitative research approach, this study utilized descriptive analysis techniques. Conducted during the even semester of the 2021/2022 academic year, the primary instrument for data collection was a rubric designed to identify scientific arguments. Findings – The findings indicate varied proficiency levels among prospective Islamic primary teacher students in identifying different components of scientific arguments. The percentage of students accurately identifying motives was 49.3%, objectives 86%, conclusions 74.7%, implications 56%, support 10%, counterarguments 13.3%, and refutations 8%. These results highlight a significant gap, particularly in identifying support, counterarguments, and refutations, suggesting that student's ability to discern scientific arguments needs substantial improvement. Research implications – The outcomes of this study are particularly valuable for universities in their efforts to enhance the argumentation skills of future teachers. Additionally, these findings will contribute to the development of effective learning strategies or models specifically tailored to improve the argumentation skills of prospective Islamic primary teacher students, thereby enhancing their academic and professional capabilities.